Sinergi Lima Bintang Guna Kebangkitan Ekonomi Bangsa Melalui Sustainability Industri Kecil Menengah Di Era Society: Studi Kasus IKM Kampung Tempe Sanan Kota Malang - Samas Adimisa Mishbah Habibie; Rida Perwita Sari (Politeknik Ganesha Medan, 2023)
This study aims to analyze the role of the five-star synergy (pentahelix) for the sustainability of small and medium industries to create a value chain that will revive the nation's economy in society era 5.0. This research method is qualitative phenomenology with pentahelix approach. This research case study was taken at the industrial center of Kampung Tempe Sanan, Malang City. The essence of this research says that the role of various parties such as the Government, Society, Academics, Media Actors, and Business Actors will have a positive impact on the sustainability of Small and Medium Industries in Society era 5.0. The role of the synergy pentahelix is to increase the capability (HR) and quality of the resulting product. So that SMEs are able to increase their profitability and create a longer value chain that has an impact on the nation's economic revival. SMEs must still be able to improve the quality and quantity of their own businesses by being willing to learn and develop. This study uses the pentahelix approach to analyze the positive power roles of various parties for the sustainability of businesses in society era 5.0. The results is revealed that SMEs Tempe Sanan actors were greatly assisted by role of various parties for sustainability of their business. The outline that can be seen from this phenomenon is the importance role of various parties for one goal, namely the revival of the nation's economy.